Thermal and acoustic analogy for the study of thermal acoustic physical properties of solid materials - V. M. Fokin; A. V. Kovylin (Vestnik MGSU)
Introduction. The article addresses the method of thermal and acoustic analogy, used to determine thermal and acoustic properties of solid building materials. A mathematical study is provided, which enables identifying parameters, dependencies and criteria characteristic of the propagation of temperature and sound waves in solid materials and to derive a new physical meaning of thermal conductivity. The mathematical experiment is confirmed by the experimental study conducted using a fluoroplastic specimen.Materials and methods. The method developed by the authors for determining a set of thermal and acoustic properties of solid materials is based on thermal and acoustic analogy. Temperature and sound vibrations (waves) propagate in a solid body according to the cosine law and are easily reproduced in laboratory conditions, which made it possible to conduct an experimental study by measuring the temperature and density of a heat flux on the surface of a specimen.Results. Experimental data on temperature and heat flow were obtained from the experiment conducted using the specimen under study, which made it possible, using the methodology developed by the authors, to identify thermal and acoustic properties of the material, including thermal conductivity, volumetric heat capacity, thermometric conductivity, surface veloci-ty of temperature waves, as well as the acoustic velocity of sound in the material. In addition, the mathematical experiment on thermal and acoustic analogy allowed the authors to establish the law of a temperature wave. Moreover, this law enabled formulating a new physical meaning of thermal conductivity of a substance.Conclusions. Experimentally identified thermal and acoustic properties of the material are consistent with the data provided in the reference and engineering literature, the discrepancy does not exceed 5 %, which confirms the validity of the mathematical experiment. Thermal and acoustic analogy makes it possible to determine not only the thermal conductivity, but also the speed of sound in materials by temperature and heat measurements taken on the surface.